PRTS: An approach for model checking probabilistic real-time hierarchical systems - SUN, Jun (Institutional Knowledge at Singapore Management University, 2011)
Model Checking real-life systems is always difficult since such systems usually have quantitative timing factors and work in unreliable environment. The combination of real-time and probability in hierarchical systems presents a unique challenge to system modeling and analysis. In this work, we develop an automated approach for verifying probabilistic, real-time, hierarchical systems. Firstly, a modeling language called PRTS is defined, which combines data structures, real-time and probability. Next, a zone-based method is used to build a finite-state abstraction of PRTS models so that probabilistic model checking could be used to calculate the probability of a system satisfying certain property. We implemented our approach in the PAT model checker and conducted experiments with real-life case studies.